2013
DOI: 10.1002/j.2161-0045.2013.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

The Psychology of Working: A Case Study of Mexican American Women With Low Educational Attainment

Abstract: Using Blustein's (2006) psychology of working and Hackman and Oldham's (1975) job characteristics theory, the authors investigated the job attribute preferences of Mexican American women with low educational attainment. They used content analysis to code and analyze the interview transcripts of 27 women. The most valued job attributes were not only those associated with survival and power but also those that incorporated aspects of social connection and self-determination, including autonomy, the opportunity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Eight of 10 participants identified that a primary reason to engage in work was survival; that is, they must work in order to earn money to support themselves. This theme has been previously noted in the literature (e.g., Blustein, , ; Guererro & Singh, ). Danielle expressed that working meets basic needs for survival: “You just have to go to work.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Eight of 10 participants identified that a primary reason to engage in work was survival; that is, they must work in order to earn money to support themselves. This theme has been previously noted in the literature (e.g., Blustein, , ; Guererro & Singh, ). Danielle expressed that working meets basic needs for survival: “You just have to go to work.…”
Section: Resultssupporting
confidence: 74%
“…For some participants, working was a means to connect with others outside of the home ( n = 5). This theme was rarely expressed in the data but is supported by previous literature (Blustein, , ; Guerrero & Singh, ). Victoria expressed the social connection enabled by engaging in work:…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Little research has explored the career development of this college population, likely because of a long history of oppression experienced by Latina women and their traditionally low educational attainment (Guerrero & Singh, 2013). With a historical lack of success in higher educational institutions, valuable information about these students has yet to be shared with counselors, researchers, educators, career advisors, or career development professionals.…”
Section: Life Roles and Valuesmentioning
confidence: 99%